Simulation Techniques Using MATLAB Simulink to Enhance The Effectiveness of Physics Lectures - Mariko, Selli; Astuti, Siwi Puji; Handayani, Santy (UNIVERSITAS INDRAPRASTA PGRI, 2025)
Difficulties in analyzing current and voltage variables in Direct Current (DC) electrical circuits remain a common challenge among students in physics courses. To address this issue, the researcher conducted action research aimed at enhancing the effectiveness of physics instruction. This study integrated the TPACK (Technological Pedagogical Content Knowledge) framework by implementing simulation-based learning through MATLAB Simulink, enabling students to visualize and analyze current and voltage behavior in DC circuits more effectively. The research adopted the Hopkins action research model, which includes the stages of problem identification, intervention planning, implementation, observation, and reflection. The findings revealed that: (1) students successfully developed DC circuit simulations using MATLAB Simulink, and (2) students demonstrated improved ability in analyzing current and voltage variables within the circuits. These results suggest that simulation-based learning grounded in the TPACK framework is a practical and effective approach for improving students’ analytical skills and conceptual understanding of DC electrical circuits, particularly in terms of current and voltage analysis.